National health accounts of Nigeria: results from second rounds of estimation (2010)
Nigeria Health Accounts (NHA) tracks the flows of health spending from financial sources to end users. This paper uses the framework to capture the general health expenditure and updates the earlier NHA for Nigeria by providing estimates for 2003-2005. The estimates were prepared in line with the WHO’s guide to the NHA estimation. Our estimates reveal that households are the major source of health funds in Nigeria. Government funding accounts for a quarter of the health funds and but the main incidence still lies with households. These funds were spent about equally in private and public health facilities. Although resource pooling is not widespread, health insurance show promise as a significant potential option in health care financing. Given health as a public good, the implication is that there is need for government focus on the responsibility to lessening the burden of health expenditure on poor households if its stewardship role is not to be called to question.